Effect of Credit Risk, Liquidity Risk, and Interest Rate Risk on Return on Assets (ROA) - Miranda, Mira (Journal of Economicate Studies, 2020)
This article discusses the effects of credit risk, liquidity risk and interest rate risk on bank profitability. The dependent variable in this study is Return On Asset (ROA). Meanwhile, the independent variables in this study are Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM).The sampling technique was done by using purposive sampling method. The total sample in this study amounted to 10 years of financial reports at PT. Bank Rakyat Indonesia (Persero) Tbk for the period 2007-2016. Data processing was performed using multiple linear regression analysis with classical assumption testing first.This article finds that partially Non Performing Loans (NPL) have a negative and significant effect on Return On Assets (ROA), Loan to Deposit Ratio (LDR) has a negative but insignificant effect on Return On Assets (ROA) and Net Interest Margin. (NIM) has a positive but not significant effect on Return on Assets (ROA), while the results of the research simultaneously state that Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) have an effect. simultaneously to Return On Asset (ROA).